The Development of English Communication Skills in the 21st Century with the Common European Framework of Reference for Languages: CEFR - Wankong, Anchanida (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 12 No 2 (2020): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
This article aims; 1) to develop the communication skills in English in the 21st century with the Common European Framework of Reference for Languages: CEFR. 2) to learn how to improve communication skills in English in the 21st century with the Common European Framework of Reference for Languages: CEFR, and 3) to understand the Common European Framework of Reference for Languages: CEFR. The 21stcentury is the period of social and learning change. Therefore, the English instructional model according to the Common European Framework of Reference for Languages: CEFR will improve the proficiency of English for communication and support teachers to arrange teaching English process effectively.